The speed of increasing milk feeds: a randomised controlled trial - Abbott, Jane; Berrington, Janet; Bowler, Ursula; Boyle, Elaine; Dorling, Jon; Embleton, Nicholas; Juszczak, Edmund; Leaf, Alison; Linsell, Louise; Johnson, Samantha; McCormick, Kenny; McGuire, William; et al. (BioMed Central, 2017)
BACKGROUND